Outcome comparison study between laparoscopic appendisectomy and conventional open appendisectomy - Sangma, Mimamaychet B.; Selvaraju, Selvakumaran; Natarajan, Pratheeba; Marak, Fremingston; Dasiah, Simon David (International Surgery Journal, 2019)
Background: Open appendisectomy (OA) had been the procedure of choice for acute appendisectomy for a century since Mc Burney introduced in 1884. Laprascopic appendisectomy (LA) didn’t gain popularity and many studies had been conducted to see the superiority of one over the other. Recent meta-analysis studies, found overall benefits in favour of LA. So, we have done comparative study with the aim to compare the benefits of LA over OA. Methods: Total of 90 appendisectomies was done, 45 each in OA and LA group and compared over a period of 1-year from October 2016 to October 2017 in Indira Gandhi Medical College and RI, Pondicherry. Outcome parameters were compared between the 2-groups in relation to operative time, analgesia used, length of post-operative hospital stay, return to work, resumption of a regular diet, post-operative scar and post-operative complications. Results: Mean age of LA was 35 years, OA was 30 years. Male preponderance observed in OA (67%), female in LA (60%). Post-operative short hospital stay was 3-days in LA, 5-days in OA. Early return to work was 9-days in LA, 15-days in OA. Operative time was significantly shorter in LA which was 30-minutes and 40-minutes in OA. In laprascopic group, no complications was observed, in open group we had two post-operative infections. Conclusions: LA is an effective and safe option and the procedure of choice for most patients regardless of age, sex and BMI, with a statistically significant finding in regards to operation time in LA compared to conventional OA group.